Effect of Yujing Jiangtang Recipe on Blood Glucose, Lipid and Serum Oxidative Stress Related Indexes in Type 2 diabetes Rats - Xiran ZHOU; Gena JIAO; Ji ZENG; Bohan LI; Lu SHEN (Shipin gongye ke-ji, 2023)
Objective: To study the effect of Yujing Jiangtang Recipe on blood glucose, lipid and antioxidation in type 2 diabetes rats. Methods: High fat diet and intraperitoneal injection of 40 mg/kg STZ were used to establish the model of type 2 diabetes rats. The successful rats were randomly divided into diabetes model group, metformin group (0.2 g/kg), low, medium and high dose Yujing Jiangtang Recipe groups (1、2、4 g/kg), and another normal control group with nine rats in each group. The treatment group was gavaged with corresponding dose, the normal control group and the diabetes model group were gavaged with 10 mL/kg normal saline according to weight, and each group was gavaged once a day for six consecutive weeks. During the experiment, observe and record the weight changes of rats in each group, and measure the fasting blood glucose (FBG). After continuous gavage for six weeks, the abdominal aorta blood of rats was taken, the fasting insulin (FINS) level and the percentage content of glycosylated hemoglobin (HbA1c) were measured, and the HOMA-IR, ISI were calculated. The contents of serum TG, TC, HDL-C, LDL-C were measured. The serum levels of MDA, SOD, GSH, NO, GSH-Px and CAT were measured by ELISA. The pancreatic tissue of rats was stained with HE to observe the pathological changes of rats. Results: Compared with the diabetes model group, the body weight of the high dose group of Yujing Jiangtang Recipe increased significantly (P<0.01). Each dose group of Yujing Jiangtang Recipe could significantly reduce FBG (P<0.01). It could reduce the levels of FINS, HOMA-IR and the percentage of HbA1c in rats to varying degrees, and increase the level of ISI (P<0.05 or P<0.01). It could reduce the content of serum TG, TC, LDL-C and MDA (P<0.05 or P<0.01), and increase the content of HDL-C and the level of SOD and GSH (P<0.01). The levels of NO, GSH-Px and CAT were significantly increased in the middle and high dose groups of Yujing Jiangtang Recipe (P<0.01). In the high-dose group of Yujing Jiangtang Recipe, the structure of exocrine gland acini was relatively complete and regular, the shape of islet cells was relatively regular, and the number of islet cells was large and evenly arranged. Conclusion: Yujing Jiangtang Recipe has hypoglycemic effect on type 2 diabetes rats, and its mechanism may be related to regulating blood lipid metabolism, improving insulin resistance, antioxidation and repairing pancreatic tissue.